Procedures of the Competent Authority in the Organization of Tourist Facilities - Lehims, Rana; Jafar, Rasha (Journal of Legal Sciences, 2023)
Tourism facilities represent one of the forms of public facilities, especially that tourism is of great importance to most of the peoples of the world and is an essential tributary to the economy and the provision of foreign currency to any country, and since the development in this field does not depend on tourism resources or tourist attractions only, but rather on how to manage them and the procedures that are practiced by the competent authorities in the management of tourist facilities are of great importance, as they bear the administrative character on the one hand and on disciplinary nature on the other hand, which was indicated during the research.